Trading Behavior of Foreign Vis a Vis Local Investors in The Indonesian Stock Market - Rahardjo, Soemarso Slamet (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This paper studies the behavior of foreign, local investors and total market in a stock trading. The analysis is focused on their implementation of positive feedback strategy, the existence of mean reverting process and their sensitivity toward expected capital gain and losses. The result reveals that both of these two investors apply the positive feedback strategy, at a different degree. The investment horizon of the foreign investors is shorter than the local investors. There is a mean reverting pattern in the price volatilities. The convergence period for local investor is 2.4. The market needs 1.8 month. No convergence period for foreign investors. The local investors and total market are neutral toward expected gain and losses. The foreign investors are more sensitive to capital loss. Previous price and volume changes have a leverage effect to the current demand of foreign investors. The local investors are affected by changes in price only.